1999
DOI: 10.1111/1467-8624.00101
|View full text |Cite
|
Sign up to set email alerts
|

Children's Social and Scholastic Lives in Kindergarten: Related Spheres of Influence?

Abstract: Evidence from two studies conducted with kindergarten samples (N = 200, M age = 5.58 years; N = 199, M age = 5.47 years) supported a series of interrelated hypotheses derived from a child x environment model of early school adjustment. The findings obtained were consistent with the following inferences: (1) Entry factors, such as children's cognitive maturity and family backgrounds, directly as well as indirectly influence children's behavior, participation, and achievement in kindergarten; (2) as children ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
783
3
50

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 899 publications
(872 citation statements)
references
References 71 publications
36
783
3
50
Order By: Relevance
“…This finding is inconsistent with previous research that has found associations between achievement and both liking and school engagement (Estell, Farmer, Cairns, & Cairns, 2002;Furrer & Skinner, 2003;Ladd, 1990;Ladd et al, 1999). The failure to find such an association may be due to the restricted range of ability in this sample.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is inconsistent with previous research that has found associations between achievement and both liking and school engagement (Estell, Farmer, Cairns, & Cairns, 2002;Furrer & Skinner, 2003;Ladd, 1990;Ladd et al, 1999). The failure to find such an association may be due to the restricted range of ability in this sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, low peer acceptance and a lack of a sense of belonging to school forecasts school avoidance and disaffected patterns of engagement (Furrer & Skinner, 2003;Guay et al, 1999). For example, Ladd et al (1999) found that peer acceptance in kindergarten predicted subsequent levels of classroom participation and achievement. Classroom engagement, in turn, is a good predictor of children's long-term academic achievement (Skinner, Zimmer-Gembeck, & Connell, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond structural aspects of classroom contexts (e.g., class size: Biddle & Berliner, 2002; % of English language learners: Gottfried, 2014), understanding the social context of classrooms-the primary learning environment of schools-has been a central goal of research focused on promotion of academic achievement and engagement (e.g., Hamre & Pianta, 2001;Ladd, Birch & Buhs, 1999;Roorda, Koomen, Spilt & Oort, 2011). Applications of social capital and attachment theories (Coleman, 1988;Dika & Singh, 2002;Pianta, 1999) suggest that specific classroom relationships provide the resources, security, and/or motivation for students to engage in academic activities.…”
Section: Introductionmentioning
confidence: 99%